The Gender Pay Gap: What Can We Learn from Northern Ireland? - Melanie K. Jones; Ezgi Kaya (Institute of Labor Economics (IZA), 2020)
Northern Ireland forms an important outlier to the established international pattern of a pronounced gender pay gap in favour of men. Using contemporary data from the Quarterly Labour Force Survey we provide a comprehensive analysis of the gender pay gap in Northern Ireland and make comparisons to the rest of the UK. Despite the relatively common institutional and policy context, the gender pay gap in Northern Ireland is found to be far smaller than in the rest of the UK. This can largely be attributed to the superior productivity-related characteristics of women relative to men in Northern Ireland, which partially offset the influence of gender differences in the returns to these characteristics. Our analysis highlights the importance of occupation â exteuro" both in terms of occupational allocation and the returns to occupations â exteuro" in explaining the cross-country differential. This is reinforced by the impact of lower earnings inequality in Northern Ireland.
Keywords: J16; J31; J24; 330; Labour Force Survey; decomposition analysis; pay discrimination; gender pay gap; Northern Ireland